Occupational Lung Cancer Surveillance in South Korea, 2006-2009 - Jong-Han Leem; Hwan-Cheol Kim; Jeong-Seon Ryu; Jong Uk Won; Jai Dong Moon; Young-Chul Kim; Sang Baek Koh; Suk Joong Yong; Soo Geun Kim; Jae Yong Park; Inah Kim; Jung Il Kim; et al. (Elsevier, 2010)
Objectives: The lung cancer mortality in Korea has increased remarkably during the last 20 years, and has been the first leading cause of cancer-related deaths since 2000. The aim of the current study was to examine the time trends of occupational lung cancer and carcinogens exposure during the period 2006-2009 in South Korea, by assessing the proportion of occupational burden. Methods: We defined occupational lung cancer for surveillance, and developed a reporting protocol and reporting website for the surveillance of occupational lung cancer. The study patients were chosen from 9 participating university hospitals in the following 7 areas: Seoul, Incheon, Wonju, Daejeon, Daegu, Busan, and Gwangju. Results: The combined proportion of definite and probable occupational lung cancer among all lung cancers investigated in this study was 10.0%, 8.6%, 10.7%, and 15.8% in the years 2006 to 2009, respectively, with an average of 11.7% over the four-year study period. The main carcinogens were asbestos, crystalline silica, radon, polyaromatic hydrocarbons (PAHs), diesel exhaust particles, chromium, and nickel. Conclusion: We estimated that about 11.7% of the incident lung cancer was preventable. This reveals the potential to considerably reduce lung cancer by intervention in occupational fields.